Significant facilitation of metal-free aerobic oxidative cyclization of imines with water in synthesis of benzimidazoles. Issue 4 (28th January 2015) - Lee, Ye-Sol; Cho, Yeon-Ho; Lee, SeungJae; Bin, Jong-Kwan; Yang, JoongHwan; Chae, GeeSung; Cheon, Cheol-Hong
Abstract: A simple, convenient, and environmentally benign protocol for the synthesis of benzimidazoles from ortho -phenylenediamines and aldehydes via aerobic oxidation was developed in wet organic solvents. Notably, water significantly accelerated this transformation, which allowed us to achieve this important transformation without the assistance of any metal catalysts and other co-oxidants. Mechanistic studies suggested that water acts as the nucleophilic catalyst for this transformation by the conversion of disfavored 5- endo - trig cyclization of imines to favored 5- exo - tet cyclization via tetrahedral intermediates and the subsequent aerobic oxidation of the resulting benzimidazolines affords benzimidazoles. Graphical abstract: